PP94 Electrochemical determination of the antioxidant activity of Laetiporus sulphureus - Ruiz Bravo, Lisette Dyanna; Martínez Suárez, Jaime Fernando; Benavides Calvache, Olga Lucía (Revista Productos Naturales, 2025)
The electrochemical behavior and antioxidant activity of L. sulphureus was performed by cyclic voltammetry (CV) and differential pulse voltammetry (DPV). For CV and DPV, a three-electrode system was used: glassy carbon working electrode, Ag/AgCl reference electrode, and platinum auxiliary electrode, using a 0.02 M acetate buffer (pH 5.0). The electrochemical behavior of L. sulphureus showed an irreversible charge transfer process centered at an anodic peak potential (Epa) of 0.52 V. Ascorbic acid presented an Epa of 0.29 V, while gallic acid exhibited two anodic peaks, at 0.41 V and 0.69 V.